Strategi Peningkatan Kualitas Manajemen Masjid di Era Digital: Studi Kasus pada Masjid Haji Keuchik Leumiek, Lueng Bata, Banda Aceh - Mujiburrahman (Jurnal Riset dan Pengabdian Masyarakat, 2026)
Digital transformation has emerged as a strategic necessity in the management of religious institutions, including mosques, in order to address demands for efficiency, transparency, and increased congregational engagement. This study aims to examine strategies for enhancing the quality of management at the Haji Keuchik Leumiek (HKL) Mosque in Banda Aceh through the utilization of digital technology. The research adopts a qualitative approach using a case study design. Data were collected through in-depth interviews with ten mosque administrators, participatory observation conducted over a three-month period, and analysis of institutional documents. Data analysis employed the interactive model proposed by Miles and Huberman, encompassing data reduction, data display, and conclusion drawing, supported by source triangulation. The findings indicate that digitalization in administrative processes, communication systems, and financial management-implemented through the eMasjid application, social media platforms, and digital dashboards-has improved operational efficiency by approximately 40% and increased congregational participation by around 30%. The primary challenges identified include limitations in digital infrastructure and insufficient technological literacy among some mosque administrators. Nevertheless, these challenges can be mitigated through continuous training initiatives and the adoption of a hybrid management approach. This study affirms that well-planned and context-sensitive digitalization of mosque management can position mosques as adaptive, transparent, and sustainable religious institutions.